Large Uncertainties in Estimation of Tropical Tropopause Temperature Variabilities Due to Model Vertical Resolution. Issue 16 (19th August 2019) - Wang, Wuke; Shangguan, Ming; Tian, Wenshou; Schmidt, Torsten; Ding, Aijun
Abstract: Tropopause temperature (TPT) is a useful indicator and a key component of climate change. Well simulating its value and seasonal‐to‐decadal variability by climate models is still challenging. How the vertical resolution influences the representation of TPT and its response to a climate forcing is largely unknown. This study investigates TPT responses to sea surface temperatures using a series of model simulations in various vertical resolution. With high vertical resolution (HV‐Res), the model gives a better representation of tropical TPTs in absolute values and seasonal variations. The corresponding changes in TPTs associated with sea surface temperature anomalies (El Niño–Southern Oscillation and Pacific Decadal Oscillation) are 30% stronger and more realistic in the HV‐Res model. Such improvements may get benefits from better representations of equatorial waves with more realistic structure and stronger interannual variations. A proper vertical resolution is therefore essential to well simulate the stratosphere‐troposphere coupling and should be used in climate change assessment. Plain Language Summary: Climate model is widely used in climate change assessment. While the horizontal resolution has been significantly improved, the vertical resolution, however, has been less concerned in model development. This study indicates that a proper vertical resolution of climate models is essential to well represent the tropical tropopause temperature (TPT, an important indicator of climate change), and its seasonal‐to‐interannual variations. The interannual variations of the TPT, which is mainly related to internal processes like ENSO, is up to 30% higher in the high vertical‐resolution model than the standard one. That means the internal variability of TPTs as well as other stratosphere‐troposphere coupled processes might be underestimated using climate models with too coarse vertical resolution. The vertical resolution should be especially concerned in model development and climate models with proper high vertical resolution should be used in climate change assessment. Key Points: The HV‐Res model represents the TPT and its interannual‐to‐decadal variations better Large uncertainties exist in estimation of TPT long‐term variabilities due to vertical resolution